2023
DOI: 10.1093/mnras/stad3341
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the discs, bulges, and intra-halo light of simulated galaxies through structural decomposition

Katy L Proctor,
Claudia del P Lagos,
Aaron D Ludlow
et al.

Abstract: We perform a structural decomposition of galaxies identified in three cosmological hydrodynamical simulations by applying Gaussian mixture models (GMMs) to the kinematics of their stellar particles. We study the resulting disc, bulge, and intra-halo light (IHL) components of galaxies whose host dark matter haloes have virial masses in the range M200 = 1011–$10^{15}\, {\rm M_\odot }$. Our decomposition technique isolates galactic discs whose mass fractions, fdisc, correlate strongly with common alternative morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 96 publications
2
4
0
Order By: Relevance
“…Preprocessing appears to be more important than mergers, but much less than stellar stripping. This result is particularly in accordance with observational studies (e.g., Joo & Jee 2023;Proctor et al 2023) that give to preprocessing/accretion a relevant role in the ICL formation. However, as mentioned in this work and discussed in C23a, this channel is not a direct way to form ICL, because the stray stars coming from preprocessing have already formed elsewhere in the past, and they are just accreted during the hierarchical formation of a given halo.…”
Section: Main Channels Of the Icl Formationsupporting
confidence: 91%
“…Preprocessing appears to be more important than mergers, but much less than stellar stripping. This result is particularly in accordance with observational studies (e.g., Joo & Jee 2023;Proctor et al 2023) that give to preprocessing/accretion a relevant role in the ICL formation. However, as mentioned in this work and discussed in C23a, this channel is not a direct way to form ICL, because the stray stars coming from preprocessing have already formed elsewhere in the past, and they are just accreted during the hierarchical formation of a given halo.…”
Section: Main Channels Of the Icl Formationsupporting
confidence: 91%
“…Not only that, our model predicts fractions that are in good agreement with the observations by Ragusa et al (2023) and Kluge et al (2021) in that halo mass range. Overall, the model agrees very well with the predictions of the Eagle project (Proctor et al 2024) up to M log 12.1 halo ~, while those of TNG50 (Ahvazi et al 2023) are biased low with respect to ours, and predict DL fractions that decrease quite importantly toward low-mass haloes. The disagreement between Eagle and TNG50 simulations, in our opinion, has to be taken with caution.…”
Section: Discussionsupporting
confidence: 83%
“…This implies also a series of results that we are going to show through the analysis below. In order to achieve our goal, we first start by showing in Figure 1 the fraction of DL as a function of halo mass and compare the predictions of our model (black lines and circles with different colors) with the results of the Eagle project (Proctor et al 2024, purple line), those of TNG50 (Ahvazi et al 2023, blue crosses), and several observed fractions from different authors (Harmsen et al 2017;Deason et al 2019;Kluge et al 2021;Ragusa et al 2023, gray symbols). The plot shows that the predictions of our model are in better agreement with observations than the other two numerical predictions, and it does agree with the Eagle project on very small scales, up to M log 12.5 halo ~if we consider the scatter (but they start to diverge from M log 12.1 halo ~).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations